2007
DOI: 10.1186/ar2115
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated delivery of IL-10 inhibits the progression of established collagen-induced arthritis

Abstract: The antibody-mediated targeted delivery of cytokines to sites of disease is a promising avenue for cancer therapy, but it is largely unexplored for the treatment of chronic inflammatory conditions. Using both radioactive and fluorescent techniques, the human monoclonal antibodies L19 and G11 (specific to two markers of angiogenesis that are virtually undetectable in normal adult tissues) were found to selectively localize at arthritic sites in the murine collagen-induced model of rheumatoid arthritis following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 51 publications
1
31
0
1
Order By: Relevance
“…We are currently investigating whether the presence of UG is able to enhance the anti-inflammatory properties of similar cytokines. In fact, it has recently been shown that an immunocytokine made up of the scFv L19 and IL10 selectively accumulates at sites of arthritis in collagen-induced arthritis experimental animal models and that it inhibits disease progression (38). The activity of this anti-inflammatory immunocytokine could be further enhanced using UG, which, again, per se possesses antiinflammatory properties and, in addition, yields a stable covalently linked homodimer.…”
Section: Discussionmentioning
confidence: 99%
“…We are currently investigating whether the presence of UG is able to enhance the anti-inflammatory properties of similar cytokines. In fact, it has recently been shown that an immunocytokine made up of the scFv L19 and IL10 selectively accumulates at sites of arthritis in collagen-induced arthritis experimental animal models and that it inhibits disease progression (38). The activity of this anti-inflammatory immunocytokine could be further enhanced using UG, which, again, per se possesses antiinflammatory properties and, in addition, yields a stable covalently linked homodimer.…”
Section: Discussionmentioning
confidence: 99%
“…Constructs containing promotors regulated by doxycycline or tetracycline were already effective in experimental arthritis [64]. Apart from gene therapy, other strategies for IL-10 targeting were studied as described by Trachsel et al, [68] where an antibody was fused with IL-10 (L19-IL-10) which accumulates at the inflamed joint and displayed a therapeutic activity [68].…”
Section: Il-10 and Rheumatoid Arthritismentioning
confidence: 99%
“…These scaffolds which release IL-10 very slowly, could be seeded with autologous chondrocytes and then implanted. The use of osmotic minipumps which secrete continuously IL-10 or an antibody mediated release of it [68,131] may be combined with gene therapeutic approaches.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…In recent clinical trials, the bacterial expression of the IL-10 transgene has shown to be biologically contained and, the treatment safe and effective in Chron's disease patients [46]. Other proposed approaches to target specific tissues are the use of fusion proteins of IL-10 and monoclonal antibodies specific for the targeted cell type, that has been shown to be effective in an experimental model of rheumatoid arthritis [48], and the chemical alteration of IL-10. IL-10 modified with mannose-6 phosphate shows a prevalent homing to the liver, in particular to fibrogenic hepatic stellate cells expressing the mannose 6 phosphate/insulin-like growth factor II receptor, and could be applied to the treatment of cirrhosis [49].…”
Section: Il-10 and Il-10 Agonistsmentioning
confidence: 99%